Bacterial Etiology of Wound Exudates in Tertiary Care Cancer Patients and Antibiogram of the Isolates. (August 2020) - Duwadi, Kiran; Khadka, Sujan; Adhikari, Sanjib; Sapkota, Sanjeep; Shrestha, Pabitra
Introduction: Patients with malignancies frequently develop infections as a result of surgical procedures and fungating wounds leading to pus formation. This cross-sectional study was conducted to explore the bacteriological spectra of infections of various cancer sites and their antibiotic sensitivity patterns among the patients visiting minor operation theatre (OT) of B.P. Koirala Memorial Cancer Hospital (BPKMCH), Chitwan, Nepal. Methods: Over a period of 3 months from September to November 2018, a total of 183 wound exudates and pus samples were collected and analyzed by standard microbiological procedures. Isolates were identified based on the colony characters, Gram staining and an array of biochemical tests. Antibiotic susceptibility testing was performed by Kirby-Bauer disc diffusion technique according to criteria set by CLSI, 2016. Methicillin resistance in Staphylococcus aureus was tested with the help of cefoxitin using disc diffusion method. Results: Out of the 183 samples, 149 (81.4%) were culture positive. Among 13 different isolates identified, S. aureus (43.0%) was predominant followed by E. coli (14.0%). Higher incidence of bacteria was seen among the males (52.3%), in the age group 51 to 60 years (26.8%) and among the patients undergoing surgical intervention to deal with cancer (34.2%). The prevalence of wound infection was significantly affected by gender, age, and treatment regimen ( P < .01). Out of the total 68 S. aureus isolates, 38 (44.1%) were deemed as Methicillin-resistant Staphylococcus aureus (MRSA). Among the 158 isolates, 85 (53.8%) were multi-drug resistant (MDR). Cefepime was the most effective antibiotic for Gram positive isolates whereas both imipenem and meropenem were found to be equally more effective for Gram negative isolates. Conclusion: This study suggests that patients with malignancies harbor pathogenic bacteria; therefore, prudent use of antibiotics is essential to prevent the emergence of MDR pathogens.